PENGUKURAN PEMEKARAN WILAYAH KABUPATEN CIREBON MENJADI KABUPATEN /KOTA BARU DENGAN METODE SKORING - Wiwiek Nurkomala Dewi; Nurul Bahiyah; Freddy Wicaksono (Jurnal Digit, 2017)
Abstract Indonesia in 1999 underwent a change of government system that had the effect of changing the implementation of governance as a whole, both central government and local government. This is marked by the enactment of Law No. 22 of 1999 on regional autonomy explaining that the system of local government is no longer fully controlled by the Central Government. The implementation of regional expansion is the process of dividing an autonomous region whether provinces, districts, or cities into two or more new autonomous regions with the aim of improving services and accelerating development. Expansion of the region into a new trend in the territorial structure of Indonesia, not least the District of Cirebon. Cirebon regency is a district in West Java Province located in the east, and borders with Central Java. The economic resources of Cirebon Regency are based on agriculture and tourism sector.The calculation and scoring methods of each indicator are scored. Scoring for provincial formation using comparison provinces, establishing districts using comparison districts and establishing cities using comparison cities. Comparative districts are the districts of the province concerned. The calculation results of the formula by comparison and scoring methods turned out to be the same decision in accordance with the application made by the computer. Using computer applications makes it easier for researchers / planners to be easier. Based on the calculation of measurement, the division of a region into a new Regency / City in Cirebon district allows to be done based on the area and the number of population. The regional expansion, whether or not a region stands to a new government area, either in the form of regency or city, large and large numbers of people, although these two factors form the basis of the founding of a new government area Keywords : measurement,expansion, region , population, scoring